2021
DOI: 10.3389/fevo.2021.687504
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Temporal Variation in Use of Residential Areas by Urban Coyotes

Abstract: Coyotes (Canis latrans) have established populations in most major urban centers across North America. While the risk of attacks on humans or their pets is low, the presence of carnivores in areas with high human use has resulted in increased public concern. Having a clearer understanding of which animals are more likely to interact with humans and when interactions are more likely to occur will help mitigate human-carnivore conflicts. Despite clear broad-scale patterns of human avoidance, human-coyote interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 61 publications
0
29
0
Order By: Relevance
“…Tis fnding was not entirely surprising, as both provinces have, for the frst time in 2013 in Alberta, recorded locally acquired cases of AE in humans [26,27,34] as well as a high prevalence of E. multilocularis in coyotes [22,25,35]. Furthermore, coyotes are increasingly found within urban communities close to homes and in dog parks [36]. Most of the afected dogs in this study had contact with wildlife (specifcally coyotes and/or foxes), visited of leash areas, and were coprophagic, all potential risk factors for canine AE.…”
Section: Discussionmentioning
confidence: 99%
“…Tis fnding was not entirely surprising, as both provinces have, for the frst time in 2013 in Alberta, recorded locally acquired cases of AE in humans [26,27,34] as well as a high prevalence of E. multilocularis in coyotes [22,25,35]. Furthermore, coyotes are increasingly found within urban communities close to homes and in dog parks [36]. Most of the afected dogs in this study had contact with wildlife (specifcally coyotes and/or foxes), visited of leash areas, and were coprophagic, all potential risk factors for canine AE.…”
Section: Discussionmentioning
confidence: 99%
“…Schell et al [ 60 ] observed captive coyote pairs over successive litters and found that parents engaged in riskier behavior (i.e., foraged more frequently) with their second versus first litters, and that parental habituation may result in reduced fear of humans in their offspring. However, in field settings, urban coyotes usually avoid people spatially [ 17 , 61 , 62 ] and temporally [ 63 ]. Young et al [ 64 ] found that coyotes that were hand-fed were more likely to subsequently approach humans and were harder to recondition towards avoidance, showing that loss of fear of humans and associated habituations are behaviors learned by individual coyotes.…”
Section: Discussionmentioning
confidence: 99%
“…Schell et al (2018) observed captive coyote pairs over successive litters and found that parents engaged in riskier behavior (i.e., foraged more frequently) with their second versus first litters, and that parental habituation may result in reduced fear of humans in their offspring. However, in field settings, urban coyotes usually avoid people spatially (Atwood et al 2004, Gerht et al 2009, Thompson et al 2021) and temporally (Gese et al 2012). Young et al (2019) found that coyotes that were hand-fed were more likely to subsequently approach humans and were harder to re-condition towards avoidance, showing that loss of fear of humans and associated habituations are behaviors learned by individual coyotes.…”
Section: Discussion (Word Count: 1087)mentioning
confidence: 99%